Severe Relapsing Clozapine-Withdrawal Catatonia - Shahrour, Tarek; Siddiq, Muez; Ghalib, Saad; Alsaadi, Taoufik (Case Reports in Psychiatry, 2015)
Catatonia as a clozapine-withdrawal syndrome has only been documented in the medical literature as case reports. We are reporting a case in which a 32-year-old man develops a catatonic state upon withdrawal of clozapine. The state was quite severe and needed ICU admission. The course was chronic and intermittent which we think was caused by the poor adherence to antipsychotics. The importance of identifying such cases early is underlined.